Improved Dielectric Properties and Grain Boundary Effect of Phenanthrene Under High Pressure - Wang, Xiaofeng; Wang, Qinglin; Qin, Tianru; Zhang, Guozhao; Zhang, Haiwa; Sang, Dandan; Wang, Cong; Li, Jianfu; Wang, Xiaoli; Liu, Cailong (Frontiers in Physics, 2021)
In situ impedance measurements, Raman measurements and theoretical calculations were performed to investigate the electrical transport and vibrational properties of polycrystalline phenanthrene. Two phase transitions were observed in the Raman spectra at 2.3 GPa and 5.9 GPa, while phenanthrene transformed into an amorphous phase above 12.1 GPa. Three discontinuous changes in bulk and grain boundary resistance and relaxation frequency with pressure were attributed to the structural phase transitions. Grain boundaries were found to play a dominant role in the carrier transport process of phenanthrene. The dielectric performance of phenanthrene was effectively improved by pressure. A significant mismatch between Z″ and M″ peaks was observed, which was attributed to the localized electronic conduction in phenanthrene. Theoretical calculations showed that the intramolecular interactions were enhanced under compression. This study offers new insight into the electrical properties as well as grain boundary effect in organic semiconductors at high pressure.